THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORKLOAD ON WORK STRESS LEVELS OF REGIONAL HOSPITAL HEALTH WORKERS RSUD. KUMPULAN PANE - Rodi Syafrizal (PT. Radja Intercontinental Publishing, 2020)
The aim of this research is to determine the influence of organizational culture and workload on the level of work stress of RSUD health workers. Tebing Tinggi City Pane Collection. The population in this study were health workers at the Kumpulan Pane Regional Hospital, totaling 46 respondents. The data source in this study came from primary data, namely from the results of collecting questionnaires which were filled in directly by the respondents. Hypothesis testing uses multiple regression analysis on the SPSS version 25 application. The results of this study show that simultaneously organizational culture and workload have a positive and significant effect on work stress levels